Effect of non-invasive transcutaneous auricular vagus nerve stimulation on cerebral motor excitability—Study protocol for a randomized, sham controlled trial - Herr, Thorsten; Kleger, Paula; Strauss, Sebastian; Szeska, Christoph; Khalil, Nura; Badran, Bashar W.; Weymar, Mathias; Grothe, Matthias (Frontiers in Neurology, 2024)
Transcutaneous auricular vagus nerve stimulation (taVNS) is becoming increasingly established in the treatment of various neurological and psychiatric diseases. However, only a few studies have focused on the overall influence of taVNS on cortical excitability in general. The planned study will investigate the effect of taVNS on the excitability of the motor cortex in young healthy subjects. The aim of the study is to gain better understand of the physiological mechanism of taVNS to contribute to new fields of application of taVNS in new areas such as the treatment of stroke or multiple sclerosis. This protocol describes a single-center, prospective, double blind, sham-controlled trial that evaluates the effect of taVNS on motor cortex excitability with a planned sample size of 30 participants. The effect of taVNS is investigated by neuronavigation and electromyography (EMG) coupled transcranial magnetic stimulation (TMS) applied before and after taVNS stimulation. The following parameters are assessed: resting motor threshold (RMT), active motor threshold (AMT), recruitment curve (RC), short intracortical inhibition (SICI), intracortical facilitation (ICF). All parameters will be assessed for taVNS on the basis of perception threshold and tolerance threshold. All investigations performed in the study were reviewed and approved by the local ethics committee of the University Medical Center Greifswald (study reference number: BB048/22). Clinical trial registration www.drks.de, number: DRKS00029937.